Implementation of an effective locomotion technique in virtual reality stress therapy - Mahalil I.; Yusof A.M.; Ibrahim N.; Mahidin E.M.M.; Rusli M.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biped locomotion; Stress relaxation; Development process; Game Engine; Joystick controllers; Locomotion technique; Motion sickness; Teleportation; Virtual reality